Rekonsiliasi Konflik Agraria di Indonesia: Studi di Desa Genteng, Sumedang Jawa Barat - Rafli Raihan Kamil; Idil Akbar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Agrarian conflict is an unavoidable reality in people's lives, especially in Genteng Village, which has experienced tensions between local communities and Perum Perhutani over land use. This article explores solutions to agrarian conflicts in Genteng Village, using desk research methods. The results of this research explain that agrarian conflicts often threaten social and economic stability, especially the case of agrarian conflict in Genteng Village, Sukasari Sub-district, Sumedang Regency, which requires reconciliation to promote sustainable development. Genteng Village has implemented participatory land mapping strategies and mediation mechanisms to resolve conflicts. Reconciliation of agrarian conflicts requires a multi-faceted approach to address the underlying factors causing disputes, involving collaboration between stakeholders, local communities, and the government to build a sustainable and inclusive land governance system.